PENGULANGAN NIKAH DALAM ADAT MASYARAKAT JAWA PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF (Studi Kasus Di Desa Jatisari Kecamatan Tempeh Lumajang) - Venny Rahmalia Silvana; Ach. Faisol; Faridatus Sa’adah (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2022)
Marriage is a human need. Marriage becomes a more prominent symbol of one's identity. In Jatisari Village, Tempeh Lumajang District, there is a tradition of repeating marriage. This tradition gave rise to many disagreements. Researchers will solve the problems that occur in these differences with the formulation of the problem as follows: (1) What are the factors causing the repetition of marriage in Jatisari Village, Tempeh Lumajang District? (2) How is the process of repeating the tradition of marriage in Jatisari Village, Tempeh Lumajang District? (3) How is the review of Islamic law and positive law about the repetition of marriage in Jatisari Village, Tempeh Lumajang District?. Methodology in this study, researchers plunge spaciousness using a qualitative approach. This study is descriptive and uses phenomenological methods. The method of data collection comes from interviews, field records, voice recordings, and documentation. The results of this study, researchers identified two factors that affect the repetition of marriage, first because the calculation of weton that does not fit and the second ihtiyat. From the opinion of jumhur scholars of the law to repeat marriage is mubah. As a solution, the repetition of marriage in Jatisari Village, Tempeh Lumajang district should be analyzed further. Keywords: Repetition of marriage, calculation of weton, Javanese